Consistency between 3 days' dietary records and 24-h urine in estimating salt intake in children and adolescents - Dong, Jie; Yu, Xiaoran; Li, Xun; Xiang, Shiting; Qin, Yongquan; Zhu, Shaolun; Zheng, Jie; Yan, Yinkun (Frontiers in Public Health, 2022)
Purpose This study aimed to evaluate the salt intake in boarding school students and the consistency between salt intake measurements based on 24-h urine and weighed dietary records over 3 consecutive days in this population. Methods This was a school-based cross-sectional study. Overweight (including obesity) or hypertensive students aged 6–14 years and their normal counterparts were recruited for this study at three boarding schools in China. Three consecutive 24-h urine samples were collected from all participants. During the collection period of 24-h urine, the weighed diet records were collected in children who had all three meals at the school canteens on weekdays. Incomplete 24-h urine or dietary records were excluded from the analysis. Results The median salt excretion was 6,218 [4,636, 8,290] mg by 24-h urine and 120 (82.2%) consumed excess salt among the participants. The median salt intake was 8,132 [6,348, 9,370] mg by dietary records and 112 (97.4%) participants consumed excess salt than recommended in participants who have all three meals in the school canteens. In children with complete dietary records and 24-h urine, the level of salt intake estimated by 24-h urine accounted for 79.6% of the dietary records. Conclusion Our study showed that boarding school students consumed excessive salt from school canteens. Thus, policies or strategies targeting school canteens are urgently needed. Weighed dietary records are recommended if feasible.